Penerapan Metode Pembelajaran Snowball Throwing untuk Meningkatkan Hasil Belajar Matematika Materi Pokok Persegi Panjang dan Persegi Pada Siswa Kelas VII-A SMP Negeri 4 Sakti - Fitria, Fitria (Journal of Technology and Literacy in Education, 2024)
The objectives of the research in this writing are: To describe the application of the Snowball Throwing method to rectangle and square material for class VII-A students of SMP Negeri 4 Sakti in the 2021 academic year. This study uses a qualitative approach with the type of classroom action research (CAR). This research was carried out in two cycles, where one cycle is divided into two meetings. In one cycle there are four stages, namely: Planning, Implementation of Action, Observation and Reflection. The data collection procedures used in this study are the observation, interview, and test methods. Based on the discussion of the research results, the research objectives to be achieved in this study are: 1) improving the abilities of teachers and students, 2) improving student learning outcomes. Students who completed the first cycle were 11 people or 56.67% and in the second cycle became 22 people or 93.33%. While students who did not complete the first cycle were 14 people or 43.33% and in the second cycle decreased to 2 people or 6.67%. So that Snowball Throwing learning has a positive impact on improving student learning achievement which is marked by an increase in student learning completion in each cycle.